PENGARUH TELENURSING TERHADAP KUALITAS HIDUP PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI CONTINUOUS AMBULATORY PERITONEAL DIALYSIS (CAPD) DI RS PGI CIKINI JAKARTA - Minar Gultom; Ni Luh Widani; Sudibyo Supardi (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
The Effect of Telenursing on the Patient's Quality of Life Chronic Kidney Disease with Continuous Ambulatory Peritoneal DialysisBackground: Chronic kidney disease is an irreversible disruption of kidney function and requires renal replacement therapy. As a substitute for continuous kidney function, one of them is Continuous Ambulatory Peritoneal Dialysis. Objective: to determine the effect of telenursing on the quality of life of the patients with chronic kidney disease undergoing Continuous Ambulatory Peritoneal Dialysis program.  Methods: This research is a quasi-experimental pretest-postest approach with control group design. The sample consisted of 60 patients, the intervention group and the control group with 30 respondents each who were taken by purposive sampling. Assessment of quality of life using the KDQOL TM36 questionnaire. Telenursing intervention through the Pd Ez Mobile application in the intervention group for 4 weeks and was observed for the 2nd and 4th weeks in June-July 2020. Results: the quality of life before the telenursing intervention was poor (60%) and after the intervention was good (73, 3). The results of the Wilcoxon different test showed a difference in telenursing services with an increase in the quality of life of 15.66 or 13.55% with a value of p = 0.000 (p <0.05). Conclusion: There was no interaction effect of telenursing use in CKD patients who underwent CAPD on improving their quality of life (p <0.05) and showed an increase in quality of life 82.2 times compared to those without telenursing intervention.